Comportamiento del consumidor y su Influenciaen las decisiones de compra en el centro comercial el paseo shhopping, cantón Quevedo, año 2015 - Montoya Monar, Martha Grivet (2015)
This research was the development of a study on consumer behavior and its influence on purchasing decisions at the mall "Walk shopping" canton Quevedo, it was created in order to observe the behavior of consumption existing customers, also managed to conclude that including variety of products are marketed; food, beverage, hardware, appliances, technology and electronics, clothing, among others. The work includes seven chapters, the same that were developed according to the importance of the issue. The first chapter refers to the contextual framework of the research, including the current problems through a diagnosis, the targets were raised, assumptions were made and the justification for the research was conducted chapter two, containing the theoretical framework where refers to the most important theory in accordance with the objectives and resolved through the theoretical, conceptual and legal foundation that served as a basis to find the results, in chapter three methods are detailed, the types are identified, and techniques and information sources are determined in addition to determining the population with the respective test sample. Chapter four highlights the results and discussion of research, achieved through market research where consumer influence was determined in their purchasing decisions in the El Paseo Shopping Mall in the city of Quevedo, data that were used to develop the respective conclusions and recommendations are the same as in the Chapter Five. In chapter six the different literature sources that were used to develop the theoretical framework of research and finally in the seventh chapter is specified which corresponds to the physical evidence of it, that is, detailed annexes.